Pengaruh Karakteristik Peternak, Penyuluhan dan Kelembagaan Kemitraan terhadap Kemampuan Budidaya Penggemukan Domba serta Dampaknya pada Pendapatan Peternak Domba (Mitra) di Kabupaten Bondowoso - Yuliana, Anita; Kustiari, Tanti; Suryadi, Ujang (Politeknik Negeri Jember, 2023)
This research aims to determine the extent of the influence of breeder characteristics, extension, partnership institutions on the ability of sheep fattening cultivation which has an impact on the income of sheep breeders (partners) in Bondowoso Regency. This research can be classified as Explanatory Research. The data acquisition method used is a questionnaire which aims to obtain detailed, factual data, facts and information by collecting recap results from respondents' answers by providing a questionnaire. The data analysis method used in this research is the Path Analysis Model. The results of this research show that breeder characteristics, sheep cultivation extension and partnership institutions have a significant effect on the ability to fatten sheep cultivation and have a significant impact on the income of breeders (partners) in Bondowoso Regency.